Systemic effect of calcium silicate-based cements with different radiopacifiers-histopathological analysis in rats - Ata, Osman; Bilge, Kubra; Yildiz, Semsettin; Dundar, Serkan; Calik, Ilknur; Ata, Asime Gezer; Bozoglan, Alihan (Peerj Inc, 2023)
Aim. This in vivo study aimed to examine the systemic effects of contemporary calcium silicate cements (CSC) contain different radiopacifiers in rats. Materials & Methods. Polyethylene tubes filled with BIOfactor MTA (BIO), Neo MTA Plus (NEO), MTA Repair HP (REP), Biodentine (DENT) and empty tubes (control group) were implanted into the subcutaneous tissues of 80 male Spraque Dawley rats for 7 and 30 days (n = 8). After 7 and 30 day, samples of liver and kidney tissues were submitted to histopathological analysis. Blood samples were collected to evaluate changes in hepatic and renal functions of rats. Wilcoxon and post hoc Dunn Bonferroni tests were used to compare between the 7th and 30th days in order to evaluate the histopathological data. Paired-sample t-test was used to compare laboratory values between the 7th and 30th days, ANOVA analysis and a post hoc Tukey test were used to compare values between groups (p < 0.05). Results. On the 7th day, REP, BIO and NEO groups were statistically similar in kidney tissue and the degree of inflammation was found to be significantly higher in these groups compared to the control and DENT groups. On the 30th day, the degree of inflammation of the REP and NEO groups in the kidney tissue was found to be significantly higher than the control, BIO and DENT groups. Although the inflammation in the liver was moderate and mild on the 7th and 30th days, no statistically significant difference was observed between the groups. Vascular congestion was evaluated as mild and moderate in kidney and liver in all groups, and no statistically significant difference was observed between the groups. While there was no statistically significant difference between the groups in the 7th day AST, ALT and urea values, when the creatinine values were compared, the DENT and NEO groups were found to be statistically similar and significantly lower than the control group. On the 30th day, ALT values were statistically similar between the groups. The AST values of the BIO group were found to be significantly higher than the DENT group. While BIO, DENT, NEO and control groups had statistically similar urea values, the REP group was found to be significantly higher than the other groups. The creatinine value of the REP group was significantly higher than the groups other than the control group (p < 0.05). Conclusion. CSCs with different radiopacifiers had similar and acceptable effects on the histological examination of the kidneys and liver systemically, and serum ALT, AST, urea, creatinine levels.
Keywords: Biocompatibility; Calcium silicate-based cement; Radiopacifier; Inflammation; Systemic effect